Effect of Social Media Marketing on Small Scale Business Performance in Ota-Metropolis, Nigeria - Adegbuyi, Omotayo Adeniyi; Akinyele, F.A.; Akinyele, S.T. (International Journal of Social Sciences and Management, 2015)
The purpose of this study is to examine the effect of social media marketing on small scale business performance. In today’s social media driven environment, it is essential that small businesses understand facebook, twitter, and the strategies behind using social media for growing their business. Unfortunately, many small businesses do not have a strategy when they begin using social media. The objectives of this study include the following: to determine how effective employee training about social media of small to medium enterprises has increase brand awareness, to examine how employee participation in SME’s operation has increase sales, to identify how continuous improvement of SME’s strategies has improve customer service, and to examine how managerial commitment of SME’s has increase the implementation of social media campaigns. One hundred and fifty copies of questionnaire were administered to owner-managers and employees of selected SME’s in Ota Metropolis of which one hundred and thirty five of the questionnaires were returned completely filled and fifteen were not returned. Four hypotheses were formulated from the structure of the research questions, ANOVA, Correlation and other statistical tools were used in testing these hypotheses. A descriptive approach is presented, followed by an in-depth structured questionnaire with the small business owners. The study reveals the different strategies the owner uses to build and maintain relationships with consumers and the study concludes with important implications for small businesses. Networking and creating relationships with other businesses, increases brand exposure. By promoting another business or their product, they may promote yours. Engaging others makes your business visible to their audience and has the potential to reach hundreds or thousands of consumers. Focusing more on relationships than sales, increases sales. Social media provides businesses the opportunity to engage their audience on many different levels, including personal. In the beginning, it is important for a business to focus on creating relationships with consumers. An owner can show interest in its audience by commenting on individual’s posts or asking questions. Doing so also exposes the business to friends of fans and followers, increasing the business’s reach. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 275-283 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12721